PERLINDUNGAN HUKUM DALAM PERKAWINAN DAN HAK WARIS DI KOTA SERANG - Inarotul Fikria; Fitria Agustin (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze legal protection in marriage and inheritance rights in Serang City, focusing on the impact of marriage legality on the legal certainty of heirs. This research employs a normative juridical method with statutory and conceptual approaches, supported by secondary data in the form of legal literature, academic journals, and previous research findings. The results indicate that although there is a strong legal foundation through the Marriage Law and the Compilation of Islamic Law, in practice there are still various problems, such as unregistered marriages (sirri marriages), low public legal awareness, and the pluralism of inheritance law systems, including Islamic law, customary law, and civil law. These conditions often lead to inheritance disputes and legal uncertainty, particularly affecting women and children as vulnerable parties. In addition, the role of Religious Courts is crucial in resolving inheritance disputes through mediation processes and fair judicial decisions, although challenges remain in terms of legal proof and differing interpretations of the law. Therefore, it is necessary to improve public legal awareness, optimize marriage registration, and strengthen the role of judicial institutions to achieve effective and equitable legal protection.